Potential Role of IL-17-Producing iNKT Cells in Type 1 Diabetes - Li, Shamin (Public Library of Science, 2014)
We explored in this study the status and potential role of IL-17-producing iNKT cells (iNKT17) in type 1 diabetes (T1D) by analyzing these cells in patients with T1D, and in NOD mice, a mouse model for T1D. Our analysis in mice showed an increase of iNKT17 cells in NOD vs control C57BL/6 mice, partly due to a better survival of these cells in the periphery. We also found a higher frequency of these cells in autoimmune-targeted organs with the occurrence of diabetes, suggesting their implication in the disease development. In humans, though absent in fresh PMBCs, iNKT17 cells are detected in vitro with a higher frequency in T1D patients compared to control subjects in the presence of the proinflammatory cytokine IL-1β, known to contribute to diabetes occurrence. These IL-1β-stimulated iNKT cells from T1D patients keep their potential to produce IFN-γ, a cytokine that drives islet β-cell destruction, but not IL-4, with a reverse picture observed in healthy volunteers. On the whole, our results argue in favour of a potential role of IL-17-producing iNKT cells in T1D and suggest that inflammation in T1D patients could induce a Th1/Th17 cytokine secretion profile in iNKT cells promoting disease development.